Characteristic study on high performance hybrid fiber reinforced concrete using copper slag fine aggregate - R. Kannan Rajkumar, P; Rahul, M; T. Ravichandran, P (International Journal of Engineering and Technology, 2018)
This study focuses on the effect on the mechanical characteristics of high performance concrete upon the utilization of copper slag in order to replace the fine aggregate. Copper slag has chemical and mechanical characteristics that can make the material a probable and efficient replacement material to river sand in concrete. On the other hand extraction of the sand from river bed in excess quantity is hazardous to the environment. River sand was partially and fully replaced (100%) by Copper slag in various proportions in the concrete. The concrete is also added with fibres in order to improve its mechanical properties. The addition of micro steel, hooked steel and polyester fibres in hybrid form with 1.0-1.25% to the total volume of concrete is found to be beneficial to the concrete. From the test results the concrete with 50% of its fine aggregate replaced with copper slag shows the better results; improved performance in compressive, split tensile, flexural strength, toughness and ductility. The addition of micro steel and hooked steel in the concrete produced a concrete of lower water absorption percentage.